MEDIA PEMBELAJARAN BERBASIS VIRTUAL MANIPULATIVE PADA MATERI FAKTA DASAR PENGURANGAN UNTUK MENINGKATKAN MOTIVASI SISWA DI KELAS INKLUSI - Adipranata, Komang Yogi; Suarjaya, I Made; Jayanta, I Nyoman Laba (Pascasarjana Universitas Pendidikan Ganesha, 2024)
Students' low motivation to understand mathematics, fundamental subtraction facts, in inclusive classes is a learning challenge. Innovation of learning media is needed that is interesting, easy to use, and able to meet the needs of students with diverse characteristics. This study aims to develop Virtual Manipulative-based learning media on basic subtraction facts to increase the motivation to learn among inclusive class students. The development model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of material experts, media experts, two teachers (homeroom teachers and special assistant teachers), and nine inclusive class III students. The instruments used included a validation sheet, a practicality questionnaire, and a learning motivation questionnaire. The study's results showed a very high level of validity (Aiken's V = 1.00) and practicality among teachers (98%) and students (87%), which is considered good. The effectiveness test showed a significance value of 0.000 (<0.05), indicating a significant increase in learning motivation. In conclusion, this Virtual Manipulative media is valid, practical, and effective, and has implications as an alternative for inclusion-friendly learning in elementary schools. The implications of this research suggest that the use of interactive technology designed to meet student needs can be an alternative for inclusion-friendly learning.